A segmentação não-convencional na escrita dos alunos do ensino fundamental II: dos erros aos acertos pela reescrita de texto - Garcia, Vera Lucia de Souza (2016)
Did the identification, description and categorization of the phenomena considered language of the non-written agreements, phonological and orthographic origin, not suitable for standard written norm, showing an increased incidence of hypo- and hyper words in the textual productions of the students. Established, then the question - problem: What factor (or factors) does (do) that there is the incidence of hypo- and hyper writing students EF-II? To answer the question and understand the nature of the targets phenomenon unconventional, its phonetic, phonological and morphological character, we rely on Mattoso House (1985) and Bisol (2001); by Abaurre; Fiad and Mayrink Sabinson (1997); Oliveira (2009), Cagliari (2009), in view of the heterogeneity of language, speech / orality / writing / literacy; we base on Corrêa (2004); Capristano (2004); Chacon (2004 and 2006) Cunha (2004 and 2010). We found that unconventional segmentation present in the writing of the subjects scribes of our research are established both in terms of prosody, specific of prosodic constituents, as due to the heterogeneous constitution of written language as individuation points Scribe by circulation in the genesis of language and the image that it makes written code institutionalized. In view of these findings, based on Abaurre; Salek Fiad; Mayrink-Sabinson and Geraldi (1995); Leal and Brandao (2006); Salek-Fiad (2009); Ruiz (2013), about writing and the rewriting of texts, we propose a roadmap of writing and rewriting text activities, focusing on students' difficulties, as reworking strategy of non-conventional segmentation - hypo- and hyper.